Prevalence of rearrangements in the 22q11.2 region and population-based risk of neuropsychiatric and developmental disorders in a Danish population: a case-cohort study. (July 2018) - Olsen, Line; Sparsø, Thomas; Weinsheimer, Shantel M; Dos Santos, Marcelo Bertalan Quintanilha; Mazin, Wiktor; Rosengren, Anders; Sanchez, Xabier Calle; Hoeffding, Louise K; Schmock, Henriette; Baekvad-Hansen, Marie; Bybjerg-Grauholm, Jonas; Daly, Mark J; et al.
Summary: Background: Although the pathogenic nature of copy number variants (CNVs) on chromosome 22q11.2 has been recognised for decades, unbiased estimates of their population prevalence, mortality, disease risks, and diagnostic trajectories are absent. We aimed to provide the true population prevalence of 22q11.2 CNVs and associated trajectory of disease risk and mortality by use of the unbiased, representative Danish iPSYCH population case cohort. Methods: This case-cohort study was done on a population of 86 189 individuals selected from the iPSYCH case cohort of 1 472 762 singletons born in Denmark between May 1, 1981, and Dec 31, 2005, who have a known mother from the Danish Civil Registration System, were residents in Denmark at 1 year of age, and enrolled in the iPSYCH Initiative. We used epidemiological methods in conjunction with nationwide hospital registers to analyse the iPSYCH case cohort of individuals with attention-deficit hyperactivity disorder (ADHD), major depressive disorder, schizophrenia, autism, or bipolar disorder and a random population-based sample. The main outcomes assessed were the population prevalence of 22q11.2 rearrangements, and associated unbiased, population-adjusted estimates and 31-year disease risk trajectories for major neuropsychiatric disorders. Findings: Population prevalence in the Danish population was one in 3672 (seven of 25 704 [0·027%; 95% CI 0·012–0·057]) for deletions and one in 1606 (17 of 25 704 [0·066%; 0·040–0·107]) for duplications. Mortality after the age of 1 year among carriers was zero, and hazard ratios for neuropsychiatric disorders ranged from 2·60 to 82·44 for both rearrangements. By the age of 32 years, about 10% of individuals with deletions or duplications had developed ADHD, autism, or intellectual disability, and deletion carriers had higher probability than duplication carriers of co-occurring intellectual disability or epilepsy. Interpretation: The significantly different prevalence of 22q11.2 duplications and deletions indicates distinct selective pressures on these rearrangements. Although risk of congenital abnormalities, developmental delay, and intellectual disability is elevated in deletion carriers, the overall prevalence of neuropsychiatric disorders is higher in duplication carriers, which implies that identification and clinical monitoring should extend beyond congenital traits and into child and adolescent psychiatry. Funding: Capital Region's Research Foundation for Mental Health Research, The Lundbeck Foundation, and US National Institutes of Health.